Co-option of hedgehog and wingless pathways in the formation of evolutionary novelties - Marialva, Marta Sofia Pires (2010)
Tese de mestrado, Biologia (Biologia Evolutiva e do Desenvolvimento), 2009, Universidade de Lisboa, Faculdade de Ciências